2005
DOI: 10.1108/01409170510785002
|View full text |Cite
|
Sign up to set email alerts
|

Layout strategies for retail operations: A case study

Abstract: The pur pose of this study was to re search re tail lay out of a lo cal su per mar ket. The five con cepts of re tail lay out were used to de ter mine if the su per mar ket was achiev ing an ef fec tive lay out. To ac com plish this study, we ap plied previ ous stud ies, con ducted in ter views, and made use of the store for our own re search. Af ter dis cov er ing that the lo cal su per mar ket needed some im provements, rec om men da tions were made to im prove the su per mar ket from the cus tom ers' point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 1 publication
0
25
0
2
Order By: Relevance
“…An optimal layout gives the ability to facilitate the access to information and aids the shopper in decision-making. Peg boards and end caps induce urge to buy impulsively (Aghazadeh, 2005). A good layout makes even the utilitarian shopper to buy additionally by creating an urge in them (Sherman et al, 1997).…”
Section: Store Environment and Urge To Buy Impulsively (Urge)mentioning
confidence: 99%
“…An optimal layout gives the ability to facilitate the access to information and aids the shopper in decision-making. Peg boards and end caps induce urge to buy impulsively (Aghazadeh, 2005). A good layout makes even the utilitarian shopper to buy additionally by creating an urge in them (Sherman et al, 1997).…”
Section: Store Environment and Urge To Buy Impulsively (Urge)mentioning
confidence: 99%
“…This is due to these major brand names had spent tons of money in selling their brands and products to the consumers, thus making supermarket's role as a middleman between marketers and consumers. Nonetheless, Aghazadeh (2005) suggested that supermarkets should place high-impulse and high-margin items that customers do not plan to purchase at the checkout counter to serve as a reminder to customers or create a mood which triggers buying intention to increase cross-selling in the store. Breath mints, gift cards, batteries, drinks, stationeries, and travel size toiletries are some of the examples of high-impulse and high-margin items that can be found at supermarkets.…”
Section: Discussionmentioning
confidence: 99%
“…Tendai ve Crispen (2009), Mehta ve Chugan (2014) ve Merugu ve Vaddadi (2017) yaptıkları çalışmalarda mağazada yer alan ürünlerin dikkat çekici şekilde sergilenmesinin doğru ve yaratıcı vitrin düzenlemeleri ile mümkün olduğunu ve vitrin düzenlemesinin de çalışmamıza paralel şekilde tüketicilerin anlık satın alma eğilimleri üzerinde anlamlı ve pozitif etkisi olduğunu belirtmişlerdir. Aghazadeh (2005) ve Hultén ve Vanyushyn (2011) vitrin düzenlemelerinin hem tüketicilerin satın alma dürtüsü (Urge to buy) hem de anlık satın alma eğilimi üzerinde anlamlı etkisinin olduğunu ifade etmişlerdir. Dolayısıyla, satışlarını artırmak isteyen perakendeciler akılcı, yaratıcı vitrin düzenlemeleri kullanarak ürün ya da marka hakkında bilgi sahibi olmayan tüketicileri bile planlı alışveriş dışına iterek anlık ve spontane olarak gerçekleşen alışverişe sevk edebilirler.…”
Section: Sonuçunclassified